An Analytical Assessment of Assurance Practices in Social Environmental and Sustainable Reporting in the United Kingdom and North America - Annisa Melissa Manurung; Hardo Basuki (Gadjah Mada International Journal of Business, 2010)
The objective of this study is to continue and extend previous studies in evaluating the extent to which current assurance practices promote transparency and accountability to stakeholders. This is carried out by conducting an empirical analysis of the content of assurance statements accompanying a sample of non-financial reports short-listed for the Association of Chartered Certified Accountants (ACCA) U.K. Sustainability Reporting Award and the CERES-ACCA Sustainability Reporting Award from 2006 to 2008. The findings of this study show that several new trends in social, environmental and sustainability assurance can be observed. Firstly, accountants tend to limit their intended readership to management only and state a disclaimer for other potential readers. This diminishes the transparency and stakeholder accountability of the reporting. Secondly, there is even stronger evidence that management has the control over the scope of the assurance engagement and over what information gets publicly disclosed. The evidence is shown in the fact that in many assurance statements prepared by accountants, only selected parts of the reports are being assured, with no indication that it is not management who selects these parts. Finally, the recent practices of assurance engagements represented by the sample in this study have not improved the transparency and stakeholder accountability of social, environmental and sustainable reporting. Similar to the two previous studies, we assert that a generally accepted standard is needed to promote assurance statements that add meaningful values to the reliability of social, environmental and sustainability reporting.